The effects of a hatha yoga-based exercises program on pain with migraine in women: A randomized controlled study - Dündar Özlem; Can Sema; Eliaçık Sinan; Yıldırım Turgut (Biomedical Human Kinetics)
Study aim: Migraine is a headache syndrome that may occur in all age groups. The purpose of this study was to examine the effects of hatha yoga (HY) exercises on pain in migraine patients.